Mental Health Indicators and Coping Strategies in Light of Some Demographic Variables among a Sample of Migrants in Jordan - Ziadat, Faten Marwan; AlSheikh Ali, Ahmad (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to identify the relationship between mental health indicators and meditation techniques among a sample of migrants in Jordan. The study also aimed to identify the differences in the averages of mental health indicators and meditation techniques according to the variables of gender, nationality, and job type. The study sample consisted of 201 male and female migrants belonging to various governorates in Jordan. Methods: The study sample consisted of 201 voluntary migrants in Jordan. The study used the descriptive correlational approach in addition to the employment of two scales of health indicators and meditation techniques. Results: The study results showed sleep problems were the most prevalent among the mental health indicators, while suicidal thoughts were less prevalent. The study results also showed that religious adaptation was mostly used, while drug use was used less. The results also showed limited differences between the two sexes, yet depression rate was higher among females and suicidal thoughts and drug use were higher among males. Arab migrants exhibited higher levels in mental health problems, while non-Arab migrants showed higher levels in drug use. Non-Arabs preferred using various meditation strategies such as active adaptation and planning, while Arabs highly relied on religious adaptation. Also, the results indicated an increasing use of drugs among workers in agriculture, industry and construction. The results evidently showed correlational relations between some mental health indicators and meditation techniques. Conclusion: The study recommends developing psychological support programs that may help migrants deal with sleep problems and address religious adaptation.